ANALISIS PROSES PEMBERIAN KREDIT DAN PENGENDALIAN INTERNAL YANG DITERAPKAN (STUDI PADA BPR â€œXâ€ KABUPATEN GRESIK) - SURYANINGRUM, PUTRI (Jurnal Akuntansi AKUNESA, 2016)
This study aims to look at how the credit granting process and internal controls applied by BPR "X" in Gresik to entrust his funds to customers and BPR sure the funds borrowed may be returned by customers. BPR "X" is one of 12 rural banks in Gresik which provide loans to total loans is high. The BPR with "X" will dare to bear the credit risk will occur. This study uses qualitative research with descriptive format. This research was conducted by direct observation to the field, interviews with the leaders and employees of the credit and the documents comprising the financial statements Accountability to see credit data. All data obtained from observation, interviews and document triangulation data to draw a conclusion. Results from this study is the BPR "X" has applied the credit granting process and internal controls with both effectively and in accordance with the theories that have been implemented in the Bank in general. And BPR "X" has an analysis of the differences with other BPR by analyzing the future cash flow at the time the customer makes a return on credit. And in the credit approval process and the internal control has a close connection to cooperate in controlling the level of non-performing loans (NPL) to keep the numbers in which the Bank is said to be healthy.